Dividing the pie: the determinants of labor's share of income on the firm level - Michael Siegenthaler; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2014)
This paper is the first to study the factors determining labor's share of income on the level of the individual firm, employing an unusually informative panel data set. The empirical examination is concerned with Switzerland which stands out as one of the very few developed countries with a stable labor share. Broadly confirming results from previous cross-country and industry-level studies, we find that the main factor decreasing the labor share in the estimation period is the increase in the share of workers using ICT in the firm. The main reasons why Switzerland's labor share remained almost constant are its relatively slow-rate of technological progress and shifts towards industries with above-average labor shares.
Keywords: D33; E25; J24; O30; 330; Labor share; factor income distribution; firm-level analysis